1993
DOI: 10.1182/blood.v81.11.2947.2947
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin G-dependent platelet stimulation by activated polymorphonuclear leukocytes and its inhibition by antiproteinases: role of P-selectin-mediated cell-cell adhesion

Abstract: Human PMN stimulated by fMLP are able to activate coincubated, autologous platelets. Cathepsin G, a neutral serine protease stored in the azurophilic granules of PMN, is the major platelet activator in this system. We previously proposed that shear-induced close PMN- platelet contact creates the conditions for which cathepsin G activity on platelets is protected against antiproteinases. The aim of this study was to investigate the adhesive mechanisms, possibly creating between PMN and platelet membranes the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 55 publications
0
25
0
2
Order By: Relevance
“…Granulocyte-mediated PLT activation requires close cellto-cell contact because proteinases released from granulocytes are quickly inactivated by plasma inhibitors. 25 PLT active factor remains mostly attached to the granulocytes' membrane. 26 The HSR of PLTs has been reported to correlate well with PLT viability and posttransfusion recovery of PLTs.…”
Section: Discussionmentioning
confidence: 99%
“…Granulocyte-mediated PLT activation requires close cellto-cell contact because proteinases released from granulocytes are quickly inactivated by plasma inhibitors. 25 PLT active factor remains mostly attached to the granulocytes' membrane. 26 The HSR of PLTs has been reported to correlate well with PLT viability and posttransfusion recovery of PLTs.…”
Section: Discussionmentioning
confidence: 99%
“…These ®ndings are indicative that neutrophils within platelet±neutrophil complexes represent an activated subset of cells. In addition, it can be inferred that the platelet component of PNCs must also represent an activated subpopulation of platelets, as CD62P expression is an essential prerequisite for PNC formation (de Bruijne Admiraal et al, 1992;Evangelista et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously shown that P-selectin mediates adhesion of flowing neutrophils to immobilized activated platelets Yeo et al, 1994), and that thrombin-activated platelets express P-selectin on their surface and bind neutrophils in suspension via this receptor (McEver, 1991;Evangelista et al 1993;Spangenberg et al, 1993). In the current study, platelet-coated microslides bound autologous neutrophils or lymphocytes.…”
Section: Discussionmentioning
confidence: 94%
“…The suspension was placed in a sterile plastic petri dish, and incubated for 30 min at 3 7°C in 5% C02 atmosphere to allow monocytes to sediment and attach to the surface. Lymphocytes were rinsed from the dish, centrifuged at 3008 for 5min and resuspended in PBS/5% plasma, counted by Coulter Counter (model ZF; Coulter Electronic Ltd, Luton) attached to a Pulse Width and Height Analyser (Fisher & Fisher, 1989), and diluted to 1 x lo6 cells/ml in the same medium. Pulse height analysis allowed assessment of the proportion of residual large Ieucocytes, outside the Iymphocyte volume peak, and this averaged N 10%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation